2013
DOI: 10.1080/01635581.2013.741759
|View full text |Cite
|
Sign up to set email alerts
|

Black Raspberry-Derived Anthocyanins Demethylate Tumor Suppressor Genes Through the Inhibition of DNMT1 and DNMT3B in Colon Cancer Cells

Abstract: We previously reported that oral administration of black raspberry powder decreased promoter methylation of tumor suppressor genes in tumors from patients with colorectal cancer. The anthocyanins (ACs) in black raspberries are responsible, at least in part, for their cancer-inhibitory effects. In the present study, we asked if ACs are responsible for the demethylation effects observed in colorectal cancers. Three days of treatment of ACs at 0.5, 5, and 25 μg/ml suppressed activity and protein expression of DNM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(81 citation statements)
references
References 22 publications
3
72
0
6
Order By: Relevance
“…Anthocyanins were also able to inhibit cell growth and are an inducer of cell apoptosis in colon cancer cells by modulating DNA damage [22][23][24] , inducing a cell cycle arrest [12,25] or are responsible for demethylation of tumour suppressor genes [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanins were also able to inhibit cell growth and are an inducer of cell apoptosis in colon cancer cells by modulating DNA damage [22][23][24] , inducing a cell cycle arrest [12,25] or are responsible for demethylation of tumour suppressor genes [26] .…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies with animal models, the same group has confirmed that dietary supplementation with black raspberries inhibits colorectal carcinogenesis by partial reactivation of epigenetically silenced Wnt regulatory genes [84,85]. They have also convincingly demonstrated that the anthocyanins, a group of polyphenols present in large quantities in black raspberries, are at least in part responsible for these effects [86].…”
Section: Foodborne Histone Deacetylase and Dna Methyltransferase Inhibimentioning
confidence: 87%
“…Further evidence from studies with CRC patients suggests that consumption of black raspberries decreases proliferation markers in colon tissue, demethylates tumor suppressor genes and modulates other biomarkers of tumor development in the human colon and rectum 96 and beneficially modulate inflammatory markers such as IL-8 97 and that these effects may be mediated by inhibition of DNA methyltransferase 1 (DNMT1). 98 …”
Section: Biological Activity and Anticancer Properties Of Berry Fruitsmentioning
confidence: 97%